Exploring Narrative Writing Skills of Indonesian 6th Graders: A Critical Genre Analysis - Fila Alfia; Lekson, Mutiara Alda; Manalu, Lidya Arella Chaterina; Parinduri, Afrahul Fadhillah; T. Thyrhaya Zein (English Lecturers and Teachers Association (ELTA), 2025)
This qualitative study examines the narrative writing skills of four 6th-grade students in Indonesia by analyzing four narrative texts and conducting interviews with the students about their writing processes. Using Bhatia’s Critical Genre Analysis (CGA) framework, the research investigates the interaction between textual features, professional practices, and cultural influences in shaping their narratives. The analysis reveals that students primarily use simple sentence structures and face challenges with grammar, such as inconsistent tense usage and subject-verb agreement errors. Additionally, their narratives reflect cultural values like family and togetherness, highlighting the role of socio-cultural norms in shaping their storytelling. Despite these strengths, the limited linguistic complexity indicates a need for instructional strategies that focus on vocabulary expansion and the development of narrative techniques. The findings also emphasize the influence of teaching practices, as most narratives follow a linear structure aligned with classroom instruction. This study contributes to educational practices by offering insights into how language, culture, and pedagogy intersect in narrative writing. The results aim to guide educators and curriculum developers in improving narrative writing instruction, enhancing its alignment with students’ developmental and cultural contexts. Keywords : Critical Genre Analysis, Education, Linguistic Features, Narrative Text